2022
DOI: 10.3390/geosciences12090328
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Factors Controlling the Duration and Productivity of Aftershocks Following Strong Earthquakes in Greece

Abstract: Strong crustal earthquakes in Greece are typically followed by aftershocks, the properties of which are important factors in seismic hazard assessment. In order to examine the properties of earthquake sequences, we prepared an earthquake catalog comprising aftershock sequences with mainshocks of Mw ≥ 5.5 from 1995 to 2021. Regional aftershock parameters were estimated to highlight variations in aftershock decay and productivity among regions with similar seismotectonic characteristics. A statistically based me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In the literature review, it was found that the earthquake related content in coursebooks was analyzed both in Türkiye (Duman Kocabaş, 2011;Kırıkkaya, Ünver and Çakın, 2011;Kılıç, 2019;Önal, 2019;Değirmenci, Kuzey and Yetişensoy, 2019;Karaca, 2022) and in the world (Morrisey, 2004;Izadkhah and Hosseini, 2005;Komac, Zorn and Ciglič, 2013;Hayashi, 2014;Seddighi et al, 2021;Li et al 2022, Seddighi et al, 2022 as part of the topic of general disasters. Both in Türkiye and in different countries around the world [Japan (Satake, 2015), USA (Gerstenberger et al, 2005), Philippines (Ong et al, 2021), China (Xiang et al, 2021), Taiwan (Chao et al, 2020), India (Hazarika and Kayal, 2022), Greece (Bonatis et al, 2022), Romania (Micu, Micu and Havenith, 2023), Canada (Eyre et al, 2022), Germany (Sach, Buchner and Schmeiden, 2020), Finland (Veikkolainen et al, 2021) etc.] earthquakes take place sometimes and negatively affect daily life.…”
Section: Bridges Between Countriesmentioning
confidence: 99%
“…In the literature review, it was found that the earthquake related content in coursebooks was analyzed both in Türkiye (Duman Kocabaş, 2011;Kırıkkaya, Ünver and Çakın, 2011;Kılıç, 2019;Önal, 2019;Değirmenci, Kuzey and Yetişensoy, 2019;Karaca, 2022) and in the world (Morrisey, 2004;Izadkhah and Hosseini, 2005;Komac, Zorn and Ciglič, 2013;Hayashi, 2014;Seddighi et al, 2021;Li et al 2022, Seddighi et al, 2022 as part of the topic of general disasters. Both in Türkiye and in different countries around the world [Japan (Satake, 2015), USA (Gerstenberger et al, 2005), Philippines (Ong et al, 2021), China (Xiang et al, 2021), Taiwan (Chao et al, 2020), India (Hazarika and Kayal, 2022), Greece (Bonatis et al, 2022), Romania (Micu, Micu and Havenith, 2023), Canada (Eyre et al, 2022), Germany (Sach, Buchner and Schmeiden, 2020), Finland (Veikkolainen et al, 2021) etc.] earthquakes take place sometimes and negatively affect daily life.…”
Section: Bridges Between Countriesmentioning
confidence: 99%
“…Furthermore, regional variability in sequence types has been widely observed and analyzed globally (Chen et al 1987;Ben-Zion et al 1993, 2006Yamanaka and Kikuchi 2004;Kanamori and Rivera 2004). For example, Bonatis et al (2022) defined six distinct tectonic regions in Greece and estimated controlling factors of the duration and productivity. Similarly, China comprises five active blocks, 26 seismic zones, and dozens of seismic subregions based on brittle failure theory of seismogenic faults (Zhang et al 2005;Qin et al 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…To explore the mechanism of earthquake sequences, scientists have conducted in-depth research on the physical environment of seismic sources. There exists general agreement that any aftershocks triggered after the main shock are mainly induced by stress adjustment during fault slip (Freed 2005;Scholz 2019;Bonatis et al 2022), whereas the migration of swarms can be partly explained by pore fluid diffusion( and other similar phenomena as suggested by Hatch et al (2020). Statistical results for mainland China further suggest that the characteristics of earthquake sequences exhibit certain regional differences due to the specific tectonic setting (Zhou et al 2001;Tian et al 2004;Jiang et al 2006b;Li et al 2011;Cheng et al 2015;Wen et al 2020).…”
Section: Introductionmentioning
confidence: 99%